CRITERIA FOR LABORATORY DIAGNOSIS OF VARIOUS FORMS EARLY CONGENITAL SYPHILIS - G. P. Martynova; N. F. Kuznetsova; A. A. Kolodina; A. B. Belkina (LLC "Diagnostics and Vaccines", 2015)
The results of clinical and laboratory (blood count) and serological monitoring of 156 children with various forms of early congenital syphilis in the initial period and the dynamics on the background of specific therapy. Violations in haemogram characterized hypochromic anemia, thrombocytopenia, leukocytosis, neytrofillezom stab shift with a sharP increase in ESR, which prevailed among the most children with the disease over polisimptomnym and significantly exceeded the level of the norm even after specific therapy. For serological examination in 84.62 % cases registered positive results in microprecipitation reaction (RMR) to 56.52% - IgM, and 97.83% - IgG reaction Enzymeimmuno assay (EIA) and 100 % - Treponema pallidum hemagglutination assay (ТРHА). On the background of specific therapy indicated positive results in the growth of bladder cancer (85.19 %), in the formulation of IgM EIA (72.22 %) and IgG (100%), thus, recorded a decline titer positivity serological RMR 2 times , IgM EIA reaction 12 times with simultaneous increase IgG positivity 4 times and 2 times in the ТРHА in the formulation of these reactions in the dynamics.